Non-intrusive inductively coupled method for condition monitoring of electrical systems - Rathnayaka Mudiyanselage Sooriya Bandara (2018)
Off-line frequency response analysis method is widely adopted as a diagnostic technique for critical electrical system, for examples, winding deformation in transformer and stator’ winding defects in induction motor. Usually, frequency response analysis detects abnormality of an electrical system by comparing its measured impedance’s frequency response with that of healthy one, which is new or has undergone a major overhaul. Off-line frequency response analysis requires shutdown of the system to be tested and therefore it lacks the real-time condition monitoring feature when the system is powered up and operates in its usual operating condition. Several on-line frequency response analysis methods have been reported but additional design and circuitries are necessary to facilitate excitation of signal and to measure the response. All these require some forms of direct electrical contacts to the system under test when it is powered by high-voltage, which can be a safety concern for personnel who handles the instrument on-site. Also, any additional circuitry to establish the electrical contact has a direct impact on the frequency response of the system under test, which can affect the accuracy of the diagnostic. This thesis proposes an on-line frequency response analysis technique that adopts a fully inductive coupling approach so that there is no direct electrical contact with the system under test, which eliminates the safety hazards. Also, the implementation is relatively easy and the installation can be done without switching off the power supply to the system. In addition, the calibration of the proposed method is relatively straightforward. Both the injecting and receiving probes can be calibrated off-line and therefore regular re-calibration of the probes without interrupting the operation of the monitored electrical system is possible, as opposed to other on-line methods that may require the monitored electrical system be switched off. The proposed method has relatively wide bandwidth that can be tailored to specific electrical system for best results. The theory behind the proposed method is described and the method validated experimentally. Using a transformer and an induction motor as system under test, on-line condition monitoring for early detection of defects is demonstrated.